2018
DOI: 10.1002/celc.201801079
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gd Doping on the Structure and Electrocatalytic Performance of TiO2 Nanotube/SnO2−Sb Nano‐coated Electrode

Abstract: Gd‐doped TiO2−NT/SnO2−Sb (NT=nanotube) electrodes were prepared by using a solvothermal synthesis approach with a nano‐sized catalyst coating. Phenol degradation and total organic carbon (TOC) removal followed pseudo‐first‐order kinetics in the experimental range. A maximum rate was achieved by using a Gd doping ratio of 2 % (molar ratio based on Gd/Sn), which was 56.5 % and 68 % higher than that of the control (Gd/0 %) for phenol degradation and TOC removal. The results from the UV scan of the electrolyte sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 29 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…Previous work on the EOP mechanism has suggested that Ni affects the mobility of lattice O, as reflected by crystallite size 16 . Other studies on doped SnO 2 have also observed that Ni and Gd doping modifies the bulk material unit cell parameters 20,53 . Figure 2 shows that the XRD peak positions of all samples are within experimental uncertainty.…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations
“…Previous work on the EOP mechanism has suggested that Ni affects the mobility of lattice O, as reflected by crystallite size 16 . Other studies on doped SnO 2 have also observed that Ni and Gd doping modifies the bulk material unit cell parameters 20,53 . Figure 2 shows that the XRD peak positions of all samples are within experimental uncertainty.…”
Section: Resultsmentioning
confidence: 58%
“…16 Other studies on doped SnO 2 have also observed that Ni and Gd doping modifies the bulk material unit cell parameters. 20,53 Figure 2 shows that the XRD peak positions of all samples are within experimental uncertainty. The Scherrer length D was also calculated from the full-width-half-max peaks in the XRD.…”
Section: Methodsmentioning
confidence: 78%
See 2 more Smart Citations
“…Among them, advanced oxidation processes (AOPs) have emerged as interesting alternatives. [4] The efficiency of these processes for removing recalcitrant pollutants from wastewaters has been widely reported in literature for a vast variety of recalcitrant pollutants: [5] pharmaceuticals, such as Propranolol and Diatrizoate; [6][7][8] dies, like Disperse Blue 3; [9,10] pesticides and herbicides, such as tebuthiuron and glyphosate; [11,12] and industrial compounds, like phenol, bisphenol A and EDTA. [13][14][15][16] Electrochemical advanced oxidation processes (EAOPs) are a particular type of AOPs that have gained increasing attention.…”
Section: Introductionmentioning
confidence: 99%